Strategies in post-photographic practice: Subverting traditional values - Sanz, Maria Andres (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2017)
After "the death of photography", after the change that has happened in the photographic field, after the processes and behaviors of the digital technique have displaced, broken and subverted the adjudicated beliefs attributed to traditional photography, the postphotography is a high potential tool inside and outside the artistic field. In this article, it is interesting to analyze the strategies that are immersed in those images that, being hybrid between the real and the virtual, invite us to reflect on questions of representation and truthfulness thanks to the self-reflection that the medium itself gives off.